Application of assignment problem in postgraduate course allocation at Ignatius Ajuru University of Education - Udok, Udeme Vincent; Victor-Edema , Uyodhu Amekauma (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study investigated the application of assignment problems in postgraduate course allocation among lecturers in the Mathematics/Statistics Department, Ignatius Ajuru University of Education (IAUE). The objectives of this study were to identify the criteria to use to ensure equity and effectiveness in postgraduate course assignment among lecturers in the Mathematics/Statistics Department through review, to determine the lecturers' effectiveness levels in postgraduate course allocation using a questionnaire and to determine the optimal solution in postgraduate course allocation based on lecturers' effectiveness levels in using Hungarian method approach. Some literatures were reviewed by various authors related to the topic of this seminar. A total of 11 lecturers were selected using the purposive sampling technique. The data used for this study was collected through an online survey questionnaire. The data was analyzed using the Hungarian method. The study period was based on second-semester postgraduate timetable schedules in the Mathematics/Statistics Department. The Hungarian method adopted for this study proved effective since all the analyses performed reached the optimal solution. However, the study recommended that the university and department should endeavour to integrate assignment problems in allocating courses to lecturers based on competence, experience and availability to achieve the maximum level of effectiveness in imparting quality education to students.